(3eSGFd hQOJ Edi GdGeGe GdefUhQ HGddg YHO Gddg Hf MeRI Hf SdjeGf hELGHJg YfgGs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdeSCdI GdChdi , bGd CjOg Gddg ai QLd GTJQi ef QLd CQVkG s
(3BNQgG (B:s
(3hef Gddg fSJeO GdJhajb hGdeYhfI , hGdSdGe Ydi cGaI GdeSdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis